A study of polybromide chain formation using carbon nanomaterials via density functional theory approach. Issue 1 (31st December 2016) - Yaya, A.; Ewels, C.P.; Efavi, J.K.; Agyei-Tuffour, B.; Kan-Dapaah, K.; Onwona-Agyeman, B.; Abavare, E.K.K.; Hassanali, Ali; Briddon, P.R.
Abstract: We use a density functional theory approach under the local density approximation (DFT/LDA) to describe the formation of polybromide chain structures, their stretching frequency modes and charge transfer induced by the interaction of these molecules with a graphene sheet. In many cases, we find polybromides to be more thermodynamically stable than the equivalent Br2 molecular structures adsorbed on graphene sheet. This results in lower frequency stretch modes at around 170–190 cm −1 . We propose that these are rarely observed experimentally due to the bromination techniques used, which introduces molecular Br2 into the carbon host material. Charge transfer with their host material means that these molecules and their associated hole charge in the neighbouring carbon materials, are then coulombically repelled from other bromine molecules which acts as a barrier to combination into polybromides. Our calculated barrier for polybromide formation (2Br2 →Br4 ) on a graphene sheet was 0.35 eV which is an exothermic process with an enthalpy value of −0.28 eV. Therefore, thermodynamically, chain polybromide formation seems to be favourable but kinetically, is unlikely, since there is an activation barrier that needs to be overcome to give stable bromine chain structures.